2012
DOI: 10.1073/pnas.1120914109
|View full text |Cite
|
Sign up to set email alerts
|

Defect in regulatory B-cell function and development of systemic autoimmunity in T-cell Ig mucin 1 (Tim-1) mucin domain-mutant mice

Abstract: Tim-1, a type I transmembrane glycoprotein, consists of an IgV domain and a mucin domain. The IgV domain is essential for binding Tim-1 to its ligands, but little is known about the role of the mucin domain, even though genetic association of TIM-1 with atopy/asthma has been linked to the length of mucin domain. We generated a Tim-1–mutant mouse (Tim-1 Δmucin ) in which the mucin domain was deleted genetically. The mutant mice showed a profound defect in IL-10 production from regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 40 publications
8
133
2
Order By: Relevance
“…Δmucin mice were found to have similar mRNA expression levels of the closest of the TIM genes in the KIM-1 locus (17). We confirmed that other TIMs, TIM-3 and TIM-4, are not differentially regulated in KIM-1…”
Section: Decreased Phagocytic Function Of Kim-1supporting
confidence: 73%
See 3 more Smart Citations
“…Δmucin mice were found to have similar mRNA expression levels of the closest of the TIM genes in the KIM-1 locus (17). We confirmed that other TIMs, TIM-3 and TIM-4, are not differentially regulated in KIM-1…”
Section: Decreased Phagocytic Function Of Kim-1supporting
confidence: 73%
“…Consistent with the absence of a significant effect of KIM-1 Δmucin BM-derived cells, it has been reported that there were very few differences found in the activity of T lymphocytes between WT and KIM-1 Δmucin mice of the same age used in this study (17). There was slightly increased IFN-γ production after activation with either plate-bound anti-CD3/CD28 or CD11c + DCs in the presence of soluble anti-CD3 (ref.…”
Section: Kim-1supporting
confidence: 66%
See 2 more Smart Citations
“…3P), which were in parallel to the frequency of IL-10 ϩ OVAsBCs in Fig. 3 Based on published data that IL-10-expressing B cells also express other cytokines (21,22), we further analyzed the phenotypes of IL-10 ϩ OVAsBCs. Positive staining of CD5, CD38, CD1d, TIM1, CD23, and CD27 was observed in 56 -78% of OVAsBCs.…”
Section: Resultsmentioning
confidence: 99%